Effects of low irradiance on growth, water uptake and yield of tomatoes grown by the nutrient film technique - Ismail, Mohd Razi; Ali, Zainab (Universiti Putra Malaysia Press, 1994)
A study was carried out on the effects of irradiance on growth and development of tomatoes grown using the Nutrient Film Technique(NFr). Plants were exposed to mean daily irradiance levels of 14. 7, 8.5, 3.3 and 0.87 MJ m-2day-l achieved by using different levels of shade. High irradiance (14.7 and 8.5 MJ m-2day-1) increased leaf area and dry weight, root and stem dry weight compared to the plants grown under lower irradiance. Plants under shade were up to 5 DC cooler than those under high irradiance. Plant water uptake and leaf nutrient concentrations in the leaves were generally lower in shaded plants than those in full sun. The highest fruit production was obtained with an irradiance of 14. 7 MJ m-2 day-l. Plants grown under 3.3 and 0.87 MJ m-2 day-J failed to fruit.